Evaluation of a candidate thermotolerant vaccine against peste des petits ruminants in Mali - Sidibé, C.A.K.; Séry, A.; Kantao, O.; Fall, Abdou; Niang, M.; Dione, Michel M. (International Livestock Research Institute, 2022)
Objective The objective of this study was to evaluate the thermotolerance profile of a PPR vaccine protocol developed by ILRI and transferred to the LCV (lot ILRI 005ND) under laboratory and field conditions.